Transparent CdO/n-GaN(0001) heterojunction for optoelectronic applications - Soylu, M.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2015)
Undoped CdO films were prepared by sol-gel method. Transparent heterojunction diodes were fabricated by depositing n-type CdO films on the n-type GaN (0001) substrate. Current-voltage (I-V) measurements of the device were evaluated, and the results indicated a non-ideal rectifying characteristic with I-F/I-R value as high as 1.17 x 10(3) at 2 V, low leakage current of 4.88 x 10(-6) A and a turn-on voltage of about 0.7 V. From the optical data, the optical band gaps for the CdO film and GaN were calculated to be 2.30 eV and 3309 eV, respectively. It is evaluated that interband transition in the film is provided by the direct allowed transition. The n-GaN (0001)/CdO heterojunction device has an optical transmission of 50-70% from 500 nm to 800 nm wavelength range. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Optical materials; Sol-gel growth; Electrical properties